The use of simulators and artificial intelligence in leadership feedback - Ntombana, Sixolile (Rhodes University, Faculty of Commerce, Department of Management)
Leadership is a key factor in team success. For leadership to succeed, leaders need to possess the requisite competencies that can facilitate their performance. Team skills is identified as a leadership competency that is prioritised and most sought after by leaders. This follows studies that confirm that team skills are vital for leadership and team success. For leadership to develop team skills, feedback must be provided. Feedback is identified as information that is provided by an observer on a particular performance. The role of feedback in leadership development serves the purposes of engagement and self-reflection and evaluation of a leader's performance. In this light, feedback cannot be separated from leadership as it is an essential part of communication in a leadership context. The nature and source of feedback can affect how the feedback is received, as shown by studies that suggest that the effectiveness of feedback goes beyond the content or nature (good/bad feedback) of the feedback. This study looks at two feedback sources: humans and artificial intelligence (AI) using students as the population. Humans have been the traditional source in feedback provision. Thus, in a team setting peers provide feedback on their peers' performances. Unprecedented technological advancements have seen the improvement of AI capabilities to being able to give feedback. This has made AI a feedback source. Following these developments, this research assessed the way in which humans and AI provide feedback and the way in which students react to feedback provided by humans and AI. The research used chatbot AI, a Skills Simulator Assessment, launched by Kotlyar (2018). Students registered for Management One at Rhodes University in 2021 were the population for this research. The research was comprised of two phases where in phase one they were assessed by the Skill Simulator Assessment and in phase two they were assessed by their peers. This research found that students are not averse to feedback from AI, although they prefer peer feedback. It was further found that peer feedback tends to be tainted by lenience, while AI is not affected by lenience. This finding marked a significant development of AI in feedback provision.
Keywords: Artificial intelligence; Leadership; Employees -- Rating of; Communication in industrial relations; Qualitative reasoning -- Technological innovations; Chatbots